Rhizosphere microbiota assemblage associated with wild and cultivated soybeans grown in three types of soil suspensions. Issue 1 (2nd January 2019) - Chang, Chunling; Chen, Wen; Luo, Shasha; Ma, Lina; Li, Xiujun; Tian, Chunjie
ABSTRACT: Soil microbial community composition is determined by the soil type and the plant species. By sequencing the V3-V4 region of the bacterial 16S rRNA gene amplicons, the current study assessed the bacterial community assemblage in rhizosphere and bulks soils of wild ( Glycine soja ) and cultivated ( Glycine max ) soybeans grown in the suspensions of three important soil types in China, including black, red and soda-saline-alkali soils. The alpha-diversity of the bacterial community in the rhizosphere was significantly higher than that of the bulk soils suggesting that bulk soil lacks plant nurturing effect under the current study conditions. Black and red soils were enriched with nitrifying and nitrogen-fixing bacteria but the soda-saline-alkali soil suspension had more denitrifying bacteria, which may reflect agronomic unsuitability of the latter. We also observed a high abundance of Bradyrhizobium and Pseudomonas, enriched cellulolytic bacteria, as well as a highly connected molecular ecological network in the G. soja rhizosphere soil. Taken all, the current study suggest that wild soybeans may have evolved to recruit beneficial microbes in its rhizosphere that can promote nutrients requisition, biostasis and disease-resistance, therefore ecologically more resilient than cultivated soybeans.